2016
DOI: 10.1002/met.1601
|View full text |Cite
|
Sign up to set email alerts
|

On quality of radar rainfall with respect to temporal and spatial resolution for application to urban areas

Abstract: In this study the quality of radar rainfall with respect to temporal and spatial resolution was examined. Gwangdeoksan Radar and the Korea Institute of Civil Engineering and Building Technology (KICT) Radar were used for this purpose, along with the automatic weather systems data within Seoul. In addition, several quantitative quality measures were applied to examine the resolution. A negative bias of more than 40% in the radar rainfall of Gwangdeoksan Radar occurred with changes in the temporal and spatial re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
8
0
2
Order By: Relevance
“…Reduced temporal resolution has more impact on the hydrological modelling accuracy than decreasing spatial resolution [12,19]. In the study by Yoon et al [19], the root mean square error and correlation coefficient increased as the accumulated time and radar bin size increased, and the correlation coefficient was found to be much more sensitive to temporal resolution than spatial resolution.…”
Section: Needs Of Urban Hydrology In Terms Of Resolution Of Precipitamentioning
confidence: 96%
See 1 more Smart Citation
“…Reduced temporal resolution has more impact on the hydrological modelling accuracy than decreasing spatial resolution [12,19]. In the study by Yoon et al [19], the root mean square error and correlation coefficient increased as the accumulated time and radar bin size increased, and the correlation coefficient was found to be much more sensitive to temporal resolution than spatial resolution.…”
Section: Needs Of Urban Hydrology In Terms Of Resolution Of Precipitamentioning
confidence: 96%
“…Reduced temporal resolution has more impact on the hydrological modelling accuracy than decreasing spatial resolution [12,19]. In the study by Yoon et al [19], the root mean square error and correlation coefficient increased as the accumulated time and radar bin size increased, and the correlation coefficient was found to be much more sensitive to temporal resolution than spatial resolution. An assessment of the impact of the temporal resolution of rainfall data on rainfall-runoff modelling was performed by, among others, Ochoa-Rodriguez et al [17], who confirmed that the influence of temporal accumulation of radar rainfall data is higher than that of spatial resolution, especially in small drainage areas.…”
Section: Needs Of Urban Hydrology In Terms Of Resolution Of Precipitamentioning
confidence: 96%
“…The attenuation correction can account for spatiotemporal differentiation depending on the rainfall type, and it also recovers the physical structure of the rainfall in accordance with the rapidly changing spatial and temporal variations as well as the spatial heterogeneity. Chandrasekar et al [14] reported that under Rayleigh scattering assumptions, radar reflectivity will not change in accordance with the radar frequency. However, the Rayleigh scattering assumptions are not strictly valid with respect to X-band.…”
Section: Introductionmentioning
confidence: 99%
“…이에 비해 기상 분야에서는 호우의 종류에 따른 강우 크기 입자분포의 변동성과 레이더 강수 추정 알고리즘의 매개변수 등을 주요 오차 원인으로 바라보고 있다 (Gosset et al, 2010). 이러한 전자, 통신, 기상 분야에서의 오차 원인을 파악하고 제거하였다 할지라도 레이더 강우를 수문분석에 활용하는 수문 전문가들에게는 여전히 레이더 강우에 오차 가 존재한다는 문제점을 제기하여 왔다 (Seo and Krajewski, 2011;Yoon, Choi, et al, 2016;Yoon et al, 2017).…”
unclassified